(untitled) (Al-Qamar, 2020)
Most of the countries in present day World are facing the problem of unemployment. Various projects are being implemented to eliminate the issue and many are under consideration. Islam also has numerous strategies in this regard. This study highlights the role of the state in addressing the problem from Ḥadīth perspective. It shows that Ḥadīth and Sunnah of Prophet Muhammad (ﷺ) has comprehensive plans to address the issue. Islamic principles based on Ḥadīth and Sunnah obligate the Islamic State to provide for the economic needs of all its inhabitants. They ensure a viable employment system supported by efficient Islamic government’s public policies.